Fluid-electrolyte balance associated with badminton match play - Ramachandran, A.; Mohan, M. (Science and Racket Sports VI, 2019)
The present study investigated fluid-electrolyte balance associated with badminton singles match play. Eight junior level female national badminton players played singles matches against matched opponents during two occasions. Pre and post match data on body weight; hematocrit; hemoglobin; serum sodium; serum potassium; urine specific gravity; urine sodium; and urine potassium were analysed form blood samples and urine samples taken before and immediately after matches. Sweat rate, quantity of fluid consumed during matches and the duration of matches were also calculated. The study results indicated significant decrease from pre to post match for body weight among the badminton players. Urine sodium showed significant decrease from pre to post match. No significant differences were observed form pre to post match for other variables. The percentage changes form pre to post match for body weight showed a range of 0.22 to 1.73% for the eight badminton players with an average of 0.99%. Sweat rate showed significant relationship to changes in body weight from pre to post match. Badminton players need to match fluid intake to sweat loss to avoid dehydration and electrolyte imbalance. Individualized advice and hydration protocol is vital for effective fluid and electrolyte balance for badminton players.